2012
DOI: 10.9721/kjfst.2012.44.1.076
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Depigmenting Effect of Carthamus tinctorius Seed, Cyperus rotundus and Schizonepeta tenuifolia Extracts

Abstract: The objective of the present study was to evaluate the skin depigmentation effect of the extracts of three herbs, Carthamus tinctorius seed, Cyperus rotundus and Schizonepeta tenuifolia. Their effects on tyrosinase and melanin synthesis inhibitory action were assessed. We found that the C. tinctorius seed ethanol extracts reduced the tyrosinase activity and melanin formation of B16F10 melanoma cells. The C. tinctorius seed suppressed the expression in microphthalmia associated transcription factor (MITF), tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…Therefore, in the current study we also assessed how inflammation (manifesting as erythema) changed during treatment, and found that, unlike HQ, CREO was also able to reduce erythema. These results support the hypothesis that axillary hyperpigmentation is a type of postinflammatory hyperpigmentation, with constant irritation from hair removal, 25,29 washing, 25 tight clothing 26 and antiperspirant use 27 among the triggering variables.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, in the current study we also assessed how inflammation (manifesting as erythema) changed during treatment, and found that, unlike HQ, CREO was also able to reduce erythema. These results support the hypothesis that axillary hyperpigmentation is a type of postinflammatory hyperpigmentation, with constant irritation from hair removal, 25,29 washing, 25 tight clothing 26 and antiperspirant use 27 among the triggering variables.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, both of the active therapies were more efficacious than placebo in treating axillary pigmentation, and topical CREO was just as effective as HQ. The whitening action of CREO can be explained by its ability to inhibit expression of microphthalmia‐associated transcription factor, tyrosinase, tyrosinase‐related protein (TRP)‐1 and TRP‐2 26 . C. rotundus has also been reported to inhibit melanogenesis in B16F10 melanoma cells 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…따라서 최근에는 세포 에 영향을 미치지 않으며 멜라닌 합성을 감소시키는 천연 미 백제에 대한 연구가 활발히 진행 중이다. 천연물을 원료로 한 미백 기능성 소재로는 신선초 [23], 마황 [32], 백출 [5], 찔레 [7], 복분자 [21] [10]. 감꼭지 추출물과 분획물에 의한 멜라노마 세포의 생존율 을 확인한 결과 (Fig.…”
Section: 서 론unclassified
“…그 중 cAMP/PKA 경로가 melanin 합성의 주요 경로로서 UV에 피부가 노출되었을 때 melanin 세포의 cAMP가 증가되고 하류 신호전달 물질인 PKA를 활성화시키 며, cAMP response element binding protein (CREB)을 거쳐 MITF의 발현을 증가시킨다 [4,5,6]. MITF는 melanin 합성 과정에서 중요한 전사 조절 인자로 Tyrosinase, TRP-1, TRP-2의 전사를 촉진한다 [7].…”
unclassified